A Functional DNase I Coating to Prevent Adhesion of Bacteria and the Formation of Biofilm. (16th January 2013) - Swartjes, Jan J. T. M.; Das, Theerthankar; Sharifi, Shahriar; Subbiahdoss, Guruprakash; Sharma, Prashant K.; Krom, Bastiaan P.; Busscher, Henk J.; van der Mei, Henny C.
Abstract: Biofilms are detrimental in many industrial and biomedical applications and prevention of biofilm formation has been a prime challenge for decades. Biofilms consist of communities of adhering bacteria, supported and protected by extracellular‐polymeric‐substances (EPS), the so‐called "house of biofilm organisms". EPS consists of water, proteins, polysaccharides and extracellular‐DNA (eDNA). eDNA, being the longest molecule in EPS, connects the different EPS components and therewith holds an adhering biofilm together. eDNA is associated with bacterial cell surfaces by specific and non‐specific mechanisms, mediating binding of other biopolymers in EPS. eDNA therewith assists in facilitating adhesion, aggregation and maintenance of biofilm structure. Here, a new method is described to prevent biofilm formation on surfaces by applying a DNase I enzyme coating to polymethylmethacrylate, using dopamine as an intermediate. The intermediate coupling layer and final DNase I coating are characterized by water‐contact‐angle measurements and X‐ray photoelectron‐spectroscopy. The DNase I coating strongly reduces adhesion of Staphylococcus aureus (95%) and Pseudomonas aeruginosa (99%) and prevents biofilm formation up to 14 h, without affecting mammalian cell adhesion and proliferation. Also agarose‐gel‐electrophoresis indicates loss of enzyme activity between 8 and 24 h. This duration however, is similar to many local antibiotic‐delivery devices, which makes it an ideal coating for biomaterial implants and devices, known to fail due to biofilm formation with disastrous consequences for patients and high costs to the healthcare system. With threatening increases in antibiotic resistance, the DNase I coating may provide a timely, potent new approach to biofilm prevention on biomaterial implants and devices. Abstract : A DNase I coating using dopamine as an intermediate layer strongly reduces bacterial adhesion and prevents biofilm formation by degradation of extracellular DNA (eDNA) in the biofilm matrix causing disruption of the matrix that holds the biofilm together, without affecting mammalian cell adhesion and proliferation.